PENGARUH LIMA DIMENSI KEPRIBADIAN TERHADAP MODAL SOSIAL (Studi Kasus di SMA se Kecamatan Kendal) (Jurnal Mahasiswa Pasca Sarjana, 2013)
Social capital is very useful for teachers because it will support the work process . Teachers who have social capital is both easy access to the wider resources so as to improve the quality , relevance , and timeliness of the information necessary for teachers to support their work.Entire study population Teachers in public and private high school in Kendal district , as many as 133 teachers . The research sample of 100 teachers with proportional random sampling technique . Data analysis and hypothesis testing using multiple regression with SPSS 16.0 for windows release . Hypothesis 1 , beta .390 on the sign . 0.000 < 0.05 , personality neoriticism positive and significant effect on dimensional structural dimension , hypothesis 2 , beta .532 on the sign . 0.000 < 0.05 , Extraversion personality positive and significant effect on the structural dimension , hypothesis 3 , beta - .312 to sign . 0.003 < 0.05 , personality Openness to new experience and a significant negative not effect on structural . Hypothesis 4 , Beta .206 to .165 sign > 0.05 , Agreeableness personality does not affect the structural dimension , hypothesis 5 Beta .183 to .041 sign < 0.05 counscientiousness positive and significant effect on the dimensions , Hypothesis 6 , beta .218 sign . 0.018 < 0.05 neoriticism positive and significant effect on the relational dimension , hypothesis 7 beta .703 sign . 0.000 < 0.05 Extraversion positive and significant effect on relational . Hypothesis 8 beta - .171 sign . 0.049 < 0.05 Openness to new experience and a significant negative not effect on relational . Hypothesis 9 .133 beta sign . .285 > 0.05 Agreeableness had no influence on the relational . Hypothesis 10 beta sign .117 .119 > 0.05 counscientiousness no effect and no significant effect on relational . Hypothesis 11 beta - sign .855 0.029 < 0.05 neoriticism negative and significant effect on cognitive , hypothesis 12 beta sign .725 0.001 < 0.05 Extraversion positive and significant effect on cognitive , sign beta.047 hypothesis 13 0.898 > 0.05 openness to new experience had no effect on cognitive capital . Hypothesis 14 beta sign .812 .127 > 0.05 Agreeableness had no effect on cognitive capital , hypothesis 15 beta sign .239 .455 > 0.05 counscientiousness no influence on the cognitive dimension of social capital. Keywords: Five Dimensions of Personality, social capital